The research aims to identify the relationship between mathematical prowess and mathematical thinking among students of the Mathematics Department in the College of Education (Journal of the College of Basic Education, 2022)
The research sample consisted of (100) male and female students from the fourth stage of the Mathematics Department.The researcher adopted the test (Al-Obaidi, 2018) for mathematical prowess, and relied on preparing the items for the Mathematical Reasoning Test on previous studies and literature. The (t) test and the Pearson correlation coefficient were used to compare the results. The results resulted in: -1- The presence of a statistically significant difference at the level of significance (0.05) between the arithmetic mean and the hypothetical average of the scores of the students of the mathematics department in the mathematical aptitude test and the mathematical reasoning test in favor of the arithmetic mean.2- The existence of a positive statistically significant correlation between the scores of students in the Mathematics Department in the Mathematical Aptitude Test and their scores in the Mathematical Reasoning Test.In light of the results of the research, the researcher concluded that the performance level of the students of the Mathematics Department was good in testing mathematical aptitude and testing of mathematical thinking and the existence of a positive correlation between mathematical prowess and mathematical thinking, and recommended a number of recommendations and proposals